Factorize the equation: take 9 and split it into its factors 3 and 3.

After factorization, determine the signs by looking at the middle term. Since it’s negative, the greater factor will be negative while the other will be positive. However, here it doesn’t make a difference because both numbers are 3.

We’re left with this

(x-3) (x-3) = 0

x-3=0 and x-3=0

By adding 3 to both sides in the first equation, we find out that x=3

The same also happens with the second equation, so x=3 as well.

Since both answers are the same, they are one solution.

## Answers ( )

Answer:x2 – 6x + 9 = 0

Step-by-step explanation:Factorize the equation: take 9 and split it into its factors 3 and 3.

After factorization, determine the signs by looking at the middle term. Since it’s negative, the greater factor will be negative while the other will be positive. However, here it doesn’t make a difference because both numbers are 3.

We’re left with this

(x-3) (x-3) = 0

x-3=0 and x-3=0

By adding 3 to both sides in the first equation, we find out that x=3

The same also happens with the second equation, so x=3 as well.

Since both answers are the same, they are one solution.